"Dangerous Rites of Passing: Staging Oneself in Multicultural America" - Šesnić, Jelena (2008)
It may be argued that “ passing” has worked as a powerful and complex representational strategy whether it be used by propagators of racial purity and a source of racial panic in maligned miscegenation, as a solicitous concern and anxiety over the rampant sexual abuse of enslaved women in the South or as employed by various African American authors in a variety of genres. It is interesting, therefore, to consider a fairly recent resurgence of attention granted to passing in several contemporary novels, which has, it seems, undergone serious reconsideration— these recent developments will be shown on the example of Philip Roth’ s powerful parable of passing turned almost on its head and enabled by the postmodern, post-Civil Rights and multicultural blurring of racial categories as demonstrated by his novel The Human Stain (2000). Even so, it will be argued that this lifting of constrictions hardly obviates the material, social and psychological effects of race. This inquiry will be complemented by anther contemporary example of this self-conscious, ironic questioning of one’ s ethnic and racial identity so ingeniously undertaken in another text, Chang-rae Lee’ s novel Native Speaker (1995). Both novels scrutinize contemporary possibilities and failures of a multicultural society to mediate the negotiation between ethnic/racial and national identities. Passing (usually but not exclusively as white), acting, impersonating, staging oneself, performing, posing as someone else, all these procedures seem to corrode the very viability of racial categories, yet their persistence as ideological strategy and fictional/plot device reinstates passing as a continuing strategy of claiming plural identities in the USA at the beginning of the new millennium.